THE UTILIZATION OF Merremia peltata FOR LIVESTOCK FEED TO CONTROL AN INVASIVE ALIEN PLANT SPECIES IN BUKIT BARISAN SELATAN NATIONAL PARK - Garsetiasih, R.; Irianto, Ragil; Sihombing, Vivin Silvaliandra (Indonesian Journal of Forestry Research, 2019)
Mantangan (Merremia peltata) is a plant species which invades the habitat of herbivorous animals such as elephants and rhinos in Bukit Barisan Selatan National Park (BBSNP) Sumatera, Indonesia. One possible way to overcome the problem is by providing M. peltata as livestock feed. This paper observes potential use of mantangan for goat feed. The study was conducted at Tampang Tua Village, a buffer zone of BBSNP where most of communities are farmers. The study and treatment were given to 6-7 months old goat breeders with an initial weight of 7-8 kg. Additional forage feed data were collected during March to June 2014. The research was designed as Latin Square Design with four treatments and four replications. The treatments consisted of four formulations namely: treatment A (field grass), B (field grass + 200 g mantangan), C (field grass + 400 g mantangan), and D (field grass + 600 g mantangan). Field grass is available continuously (ad-libitum). Results shows that the treatments significantly affect feed consumption level (P <0.05), but it did not have significant effect to body weight (P> 0.05). In other words, mantangan is potential for animal feed. This research was conducted as an effort to manage invasive alien plant species by utilizing mantangan as feed for livestock.